Accurate 8-Node Hybrid Hexahedral Elements with Energy-Compatible Stress Modes (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, an energy-compatibility condition is used forstress optimization in the derivation of new accurate 8-nodehexahedral elements for three-dimensional elasticity.Equivalence of the proposed hybrid method to an enhancedstrains method is established, which makes it easy to extendthe method to general nonlinear problems. Numericaltests show that the resultant elements possess high accuracy atcoarse meshes, are insensitive to mesh distortions and freefrom volume locking in the analysis of beams, plates and shells.